Effects of parental short message service reminders on infant immunisation coverage,timeliness and barriers in Nigeria: A quasi-experimental study - Hamina Dathini; Siti Khuzaimah Ahmad Sharoni; Kever Robert (Malaysian Family Physician)
Introduction: This study aimed to determine the effects of parental short message service (SMS) reminders on infant immunisation coverage, timeliness and barriers and evaluate the effects of sex on immunisation outcomes in Maiduguri, Borno State, Nigeria. Methods: This two-arm quasi-experimental study was conducted in two primary healthcare facilities selected using simple random sampling with opaque envelopes. A total of 524 participants were enrolled using purposive sampling. Data were statistically analysed using the Statistical Package for the Social Sciences version 28 with repeated-measures logistic regression analysis, the Z test for Poisson rates and the Wilcoxon signed-rank test. Results: The parental SMS reminders significantly improved the immunisation coverage, as reported by 69 (26.3%) (P=0.001, 95% confidence interval [CI]=12.2–40.5), 117 (44.7%) (P=0.001, 95% CI=32.6–56.9) and 116 (44.3%) participants (P=0.001, 95% CI=34.2–54.4) for the 6th-, 10th and 4th-week schedules, respectively. Compared to mothers’ involvement, fathers’ involvement did not significantly affect the immunisation coverage (B=0.158, P=0.311, 95% CI=−0.148–−0.464). With regard to the immunisation timeliness, the parental SMS reminders yielded a significant effect for the 6th-, 10th- and 14th-week schedules (P=0.001, 95% CI=25.9–46.7; P=0.001, 95% CI=24.2–43.0; and P=0.001, 95% CI=21.1–36.9, respectively). Compared to mothers’ involvement, fathers’ involvement significantly influenced the immunisation timeliness (B=0.298, P=0.038, 95% CI=0.016–0.579). Lastly, the parental SMS reminders significantly reduced the barriers to immunisation, with a P-value of 0.001. Conclusion: Parental SMS reminders can significantly improve immunisation outcomes in Nigeria.